Preferential Tax Treatment of Capital Gains, Optimal Dividend Policy, and Capital Budgeting - Pye, Gordon (Quarterly Journal of Economics, 1972)
I. Introduction and summary, 226. — II. Valuation, 228. — III. Optimal dividend policy, 229. — IV. An empirical test, 234. — V. Comparative statics, 235. — VI. Capital budgeting, 237. — VII. Policy implications, 241.